2020
DOI: 10.1186/s12859-020-3358-4
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach on multiscale texture analysis for breast microcalcification diagnosis

Abstract: Background: Screening programs use mammography as primary diagnostic tool for detecting breast cancer at an early stage. The diagnosis of some lesions, such as microcalcifications, is still difficult today for radiologists. In this paper, we proposed an automatic binary model for discriminating tissue in digital mammograms, as support tool for the radiologists. In particular, we compared the contribution of different methods on the feature selection process in terms of the learning performances and selected fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Although these differences can be minimized through the use of computer-aided detection systems in MRI, as documented in the literature for other breast imaging methods [24][25][26][27][28][29], our study demonstrated that there is a significant difference in all the breast lesions in the images from the prone and the supine position with the exception of the fibroadenomas, the single papilloma, the lymph nodes and a silicoma, benign formations of the breast and invasive ductal carcinoma. In the remaining cases, a significant variation in the extension was observed, which generally consisted of a reduction in the extension in the prone compared to the supine position.…”
Section: Discussionsupporting
confidence: 48%
“…Although these differences can be minimized through the use of computer-aided detection systems in MRI, as documented in the literature for other breast imaging methods [24][25][26][27][28][29], our study demonstrated that there is a significant difference in all the breast lesions in the images from the prone and the supine position with the exception of the fibroadenomas, the single papilloma, the lymph nodes and a silicoma, benign formations of the breast and invasive ductal carcinoma. In the remaining cases, a significant variation in the extension was observed, which generally consisted of a reduction in the extension in the prone compared to the supine position.…”
Section: Discussionsupporting
confidence: 48%
“…The performance of the model depends on how the data are split, which could lead to errors in its evaluation. An N-fold cross-validation method is potentially more effective for deep learning based on multiple training-validation splits and should provide a better indication of how well a model would perform given new previously unseen data [27,28]. An N-fold approach is currently beyond the capability of our resources, but future research will investigate whether an n-fold cross-validation method can be used to construct a highly accurate and stable AI system.…”
Section: Discussionmentioning
confidence: 99%
“…The microcalcification clusters, which are indicated in the VABB biopsy, if visible at ultrasound, are also easily and immediately sampled with Elite VABB, thus reducing the percentage of the stereotaxic VABBs and promoting a saving in terms of cost, time, and personnel (due to the absence of a radiological technician). This acknowledgement could increase further in the future in the event of development in automatic systems of detection and characterization of such specimens even in ultrasound as present in mammography [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%